DETEKSI DINI GIZI KURANG DAN RISIKO GAGAL TUMBUH: URGENSI PEMANTAUAN RUTIN DI USIA GOLDEN AGE - Heri Yusuf Muslihin; Aini Loita; Yayu Fauziah; Nazwa Rahmadani; Masturoh, Sopi (LPPM IAD Probolinggo, 2025)
The golden age (0–5 years) is a critical period for children's growth and development, so early detection of malnutrition and the risk of growth failure is crucial to prevent long-term impacts. This study aims to explore the urgency of routine monitoring of early childhood nutritional status and identify risk factors for growth failure. The research method used a descriptive qualitative approach with field observation techniques on 40 children aged 0–72 months at the Ciroyom Integrated Health Post (Posyandu), Tasikmalaya. Data were collected through anthropometric measurements, parent interviews, and developmental examinations using the Pre-Screening Development Questionnaire (KPSP), hearing, and vision tests. The results showed that some children experienced stunting and wasting, as indicated by z-scores below WHO standards. Causal factors include a lack of parental nutritional knowledge, suboptimal parenting patterns, unhygienic environments, and recurrent infections. The conclusion of this study confirms that routine monitoring through Posyandu and comprehensive growth and development detection are essential as early intervention strategies to prevent growth failure in early childhood. Keywords: early detection; malnutrition; growth failure; early childhood; golden age